Blockade of the pro‐fibrotic reaction mediated by the miR‐143/‐145 cluster enhances the responses to targeted therapy in melanoma. Issue 3 (14th February 2022) - Diazzi, Serena; Baeri, Alberto; Fassy, Julien; Lecacheur, Margaux; Marin‐Bejar, Oskar; Girard, Christophe A; Lefevre, Lauren; Lacoux, Caroline; Irondelle, Marie; Mounier, Carine; Truchi, Marin; Couralet, Marie; et al.
Abstract: Lineage dedifferentiation toward a mesenchymal‐like state displaying myofibroblast and fibrotic features is a common mechanism of adaptive and acquired resistance to targeted therapy in melanoma. Here, we show that the anti‐fibrotic drug nintedanib is active to normalize the fibrous ECM network, enhance the efficacy of MAPK‐targeted therapy, and delay tumor relapse in a preclinical model of melanoma. Acquisition of this resistant phenotype and its reversion by nintedanib pointed to miR‐143/‐145 pro‐fibrotic cluster as a driver of this mesenchymal‐like phenotype. Upregulation of the miR‐143/‐145 cluster under BRAFi/MAPKi therapy was observed in melanoma cells in vitro and in vivo and was associated with an invasive/undifferentiated profile. The 2 mature miRNAs generated from this cluster, miR‐143‐3p and miR‐145‐5p, collaborated to mediate transition toward a drug‐resistant undifferentiated mesenchymal‐like state by targeting Fascin actin‐bundling protein 1 (FSCN1), modulating the dynamic crosstalk between the actin cytoskeleton and the ECM through the regulation of focal adhesion dynamics and mechanotransduction pathways. Our study brings insights into a novel miRNA‐mediated regulatory network that contributes to non‐genetic adaptive drug resistance and provides proof of principle that preventing MAPKi‐induced pro‐fibrotic stromal response is a viable therapeutic opportunity for patients on targeted therapy. Synopsis: This study identifies a critical miRNA‐mediated regulatory axis controlling melanoma cell phenotypic adaptation and resistance to MAPK inhibitors (MAPKi) and targetable by the anti‐fibrotic drug nintedanib. The fibrosis‐associated miR‐143/‐145 cluster is upregulated by targeted therapy and highly expressed in MAPKi‐resistant BRAF‐mutated melanoma displaying a pro‐fibrotic dedifferentiated mesenchymal‐like phenotype. The two mature miRNAs miR‐143‐3p and miR‐145‐5p promote a dedifferentiated, slow‐cycling and invasive phenotype associated with altered ECM production and therapy resistance. F‐acting bundling protein Fascin1 (FSCN1) appears as a key functional target of both miRNAs to promote transition towards this therapy‐resistant phenotype. The miR‐143/‐145/FSCN1 axis regulates actin cytoskeleton dynamics and YAP/MRTF‐dependent mechanopathways. Nintedanib prevents miR‐143/‐145 cluster upregulation and combination therapy with MAPKi and nintedanib normalizes the tumor ECM niche and delays relapse in an allograft melanoma model. Abstract : This study identifies a critical miRNA‐mediated regulatory axis controlling melanoma cell phenotypic adaptation and resistance to MAPK inhibitors (MAPKi) and targetable by the anti‐fibrotic drug Nintedanib.